Exploring the potential of telemedicine for improved primary healthcare in India: a comprehensive review - Ashwaghosha Parthasarathi; Tina George; Muruga Bharathy Kalimuth; Sudhindra Jayasimha; Mohammed Kaleem Ullah; Rutuja Patil; Ajay Nair; Urvi Pai; Esther Inbarani; Anil G. Jacob; V.J. Chandy; Oommen John; et al. (Elsevier, 2024)
Summary: Telemedicine is a promising solution to the challenges of delivering equitable and quality primary healthcare, especially in LMICs. This review evaluated peer-reviewed literature on telehealth interventions in Indian primary care published from Jan 1, 2011 to Dec 31, 2021, from PubMed, Scopus, TRIP, Google Scholar, Indian Kanoon, and Cochrane database The majority of Indian studies focus on key health issues like maternal and child health, mental health, diabetes, infectious diseases, and hypertension, mainly through patient education, monitoring, and diagnostics. Yet, there's a lack of research on telemedicine's cost-effectiveness, communication among providers, and the role of leadership in its quality and accessibility. The current research has gaps, including small sample sizes and inconsistent methodologies, which hamper the evaluation of telemedicine's effectiveness. India's varied healthcare landscape, technological limitations, and social factors further challenge telemedicine's adoption. Despite regulatory efforts, issues like the digital divide and data privacy persist. Addressing these challenges with a context-aware, technologically driven approach is crucial for enhancing healthcare through telemedicine in India.